(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Working capital is required for the smooth functioning of routine operations of a business. Business organizations that is having ample amount of working capital can confidently claim for long-term success of business. Then on the other hand working capital also provides a basis for meeting the objectives of all the respective stakeholders of business like wealth creation, management of cash, etc. Rather working capital is a kind of assurance for long term success of the organization. This present study evaluates the stature of working capital in case of MSMEand the area of study is Madhya Pradesh. The researcher has considered 50 organizationsregistered under MSME in all the three modes i.e. Micro, Small and medium. The study includesboth the primary and secondary data. Considering a broader view, companies do need working capital to manage the current assets and liabilities and maintaining the equilibrium between the two. Likely the management of working capital is in close contact with the current assets and liabilities. In another sense it can be stated that adequate working capital is required i.e. not more than or less than the requirement. For any of the given firm, the policy followed in terms of working capital is very important because the amount endorsed as the part of working capital is having its impact on the liquidity, profitability and overall health of the organization